2004
DOI: 10.1623/hysj.49.3.413.54347
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of human activities on the water–land environment of the Shiyang River basin, an arid region in northwest China / Les impacts des activités humaines sur l’environnement pédo-hydrologique du bassin de la Rivière Shiyang, une région aride du nord-ouest de la Chine

Abstract: (2004) The impacts of human activities on the water-land environment of the Shiyang River basin, an arid region in northwest China / Les impacts des activités humaines sur l'environnement pédo-hydrologique du bassin de la Rivière Shiyang, une région aride du nord-ouest de la Chine, Hydrological Sciences Journal, 49:3, Abstract The Shiyang River basin is a typical interior river basin that faces water shortage and environmental deterioration in the arid northwest of China. Due to its arid climate, limited wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…The present study indicated that surface FS + N regime conserves higher soil moisture across the growing season principally during early growth stages compared with CK. The surface application of mulching acts as a physical barrier for reducing evaporation losses, reduces rainfall water runoff and thus increases water storage and slows down air convection on the soil surface (Kang et al 2004, Fan et al 2013. Furthermore, the FS + N regime enhanced soil water storage, so that CK -no straw mulching and no nitrogen; N -no straw mulching and 172 kg N/ha; HS + N -half straw mulching at a rate of 2500 kg/ha of wheat straw with 172 kg N/ha; FS + N -full straw at a rate of 5000 kg/ha of wheat straw with 172 kg N/ha.…”
Section: Resultsmentioning
confidence: 99%
“…The present study indicated that surface FS + N regime conserves higher soil moisture across the growing season principally during early growth stages compared with CK. The surface application of mulching acts as a physical barrier for reducing evaporation losses, reduces rainfall water runoff and thus increases water storage and slows down air convection on the soil surface (Kang et al 2004, Fan et al 2013. Furthermore, the FS + N regime enhanced soil water storage, so that CK -no straw mulching and no nitrogen; N -no straw mulching and 172 kg N/ha; HS + N -half straw mulching at a rate of 2500 kg/ha of wheat straw with 172 kg N/ha; FS + N -full straw at a rate of 5000 kg/ha of wheat straw with 172 kg N/ha.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the precipitation occurs during the June-through-August period of the year. Mean annual runoff in the Shiyang River is about 15.75 Â 10 8 m 3 yr À1 , whereas in the Hei River it is about 37.7 Â 10 8 m 3 yr À1 (Kang et al, 2009).…”
Section: Study Areamentioning
confidence: 97%
“…Long term average data (1950e2000) show that precipitation and potential ET (based on calculations with the Penman-Monteith equation; Monteith, 1965;Penman, 1948) in the deserts are approximately 80e150 mm yr À1 and 2300e2600 mm yr À1 , respectively. Corresponding figures for the mountainous regions are 300e600 mm yr À1 for precipitation and about 700 mm yr À1 for potential ET (Akiyama et al, 2007;Chen et al, 2005;Gates et al, 2008;Huo et al, 2008;Kang et al, 2009;Ma et al, 2013;Tong et al, 2007;Wang and Cheng, 1999;Wang and Zhao, 2011;Zang et al, 2012). Most of the precipitation occurs during the June-through-August period of the year.…”
Section: Study Areamentioning
confidence: 99%
“…Most of the precipitation occurs during June to August; about 94 % of water delivered from the mountains to lowland oases is through surface runoff. Average annual runoff in the Shiyang River is about 15.8 × 10 8 m 3 yr −1 , whereas in the Hei River it is about 37.7 × 10 8 m 3 yr −1 (Kang et al, 2009). …”
Section: Study Areamentioning
confidence: 98%